PENGGUNAAN STRATEGI TEAMS GAMES TOURNAMEN (TGT) UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM( PAI ) SISWA KELAS XI IPS 3 SMA NEGERI 1 SALO: Improving Learning Outcomes of Learners Using Cooperative Learning Model Three - Step Interview on the Geometry Room in Class XII MIPA 2 SMA Negeri 2 Pekanbaru - Hazmiati, M.Pd.I, Hazmiati, M.Pd.I (Perspektif Pendidikan dan Keguruan, 2018)
Classroom action research has been carried out at SMA Negeri 1 Salo in the subjects of Islamic Religion Education (PAI) with the object of research of class XI IPS 3 students in odd semester 2016/2017. This research was conducted in an effort to improve the PAI learning outcomes for students of class XI IPS 3. Teams Games Tournament (TGT) learning model was chosen to be applied after going through the results of observation and reflection conducted by researchers. Researchers plan actions based on the results of observations and reflections that have been made through the preparation of learning-based learning tools Teams Games Tournament (TGT) which consists of test questions, observation sheets and learning plans and other supporting learning tools. Teams Games Tournament (TGT) learning model consists of 3 main stages: knowing the material, working on the activity sheet, and playing academic games. This research can be completed in 2 cycles of 6 meetings and post tests at the end of each meeting. The results of the study which are observational data and recapitulation of results and recapitulation of learning completeness shows that there has been an increase in positive student learning activities in the classroom and an increase in the mean of the test and an increase in classical completeness of cycle 1 with cycle 2. The average pre-action score is 42.72 (enough) The average value in cycle 1 is 51.84 (enough). The average score in cycle 2 was 76.16 (good). The activity of students during the learning process was observed by observers as data for evaluation and reflection. The recapitulation of the average test and the completeness of the study was obtained from the post test scores of cycles I and II. Based on the results of the study, it can be concluded that the implementation of the Tams Games Tournament (TGT) strategy in class XI IPS 3 of SMA Negeri 1 Salo is able to improve the learning outcomes of PAI subjects (Islamic Education) as indicated by the average test and classical completeness in each cycle.